On-site analysis of cortisol in saliva based on microchannel lateral flow assay (mLFA) on polymer lab-on-a-chip (LOC). - Upaassana, V. Thiyagarajan; Setty, Supreeth; Jang, Heeyeong; Ghosh, Sthitodhi; Ahn, Chong (Biomedical Microdevices, 2025)
Unbound cortisol in saliva, detectable through non-invasive sampling, is widely recognized as a validated biomarker for the biochemical evaluation of common mental disorders such as chronic stress, depression, anxiety, and post-traumatic stress disorder (PTSD). In this work, we report a novel polymer lab-on-a-chip (LOC) for microfluidic lateral flow assay (mLFA) with on-chip dried reagents for the detection of unbound cortisol in saliva using a competitive immunoassay protocol. The new polymer microchannel lateral flow assay on lab-on-a-chip (mLFA-LOC), replicated using injection molding technology, are composed of sequentially connected microchannels for sample loading, detection antibody immobilization, flow delay, sensing spirals for test and control, and a capillary pump at the end. The competitive immunoassay of cortisol can be autonomously performed through the microchannels after sample loading of the filtered saliva, and the fluorescence signals emitted from the sensing spirals are detected and quantified by a custom-designed, portable fluorescence analyzer developed in this work. For the evaluation of cortisol assay, artificial saliva samples spiked with unbound cortisol were analyzed using mLFA-LOC and the portable analyzer. The performed competitive assay of unbound cortisol showed a limit of detection (LoD) of 1.8 ng/mL and an inter-chip coefficient of variation (CV) of 4.0%, which covers the clinical range for on-site unbound salivary cortisol analysis. The newly developed mLFA-LOC platform certainly works successfully for the rapid on-site sampling and analysis of salivary biomarkers.